Impact of depression on personal hygiene practices- A cross-sectional study among university students in Bangladesh - Fouzia Akter; Akibul Islam Chowdhury; Md. Nawal Sarwer (PLoS ONE, 2025)
Background This study explores the relationship between depression and personal hygiene practices among university students in Bangladesh. Methods A cross-sectional online survey was conducted, utilizing an 18-item Personal Hygiene Practice Questionnaire (PHPQ) and the Center for Epidemiologic Studies Depression Scale (CES-D) to assess hygiene behaviors and depression risk among 1,913 undergraduate students in Dhaka, Bangladesh. Data were analyzed using chi-square test and ordered logistic regression. The PHPQ was validated through item analysis, internal consistency, construct validity and reliability tests. Results A high prevalence of depression risk was revealed with 79.9% of females and 73.9% of males. Females demonstrated superior hygiene practices, with 90.1% classified as having good hygiene compared to 75.0% of males. Accommodation type significantly influenced both depression and hygiene, as students living in privately managed housing exhibited better hygiene practices (88.6% good hygiene) and lower depression risk (73.2%) compared to those living at home (79.2%) or in university housing (78.7%). Ordered logistic regression analysis indicated that students at risk of depression had 65% lower odds of maintaining better hygiene practices (OR = 0.36, p < 0.001), and male students were 68% less likely to have higher hygiene scores than females (OR = 0.32, p < 0.001). The Exploratory Factor Analysis and Cronbach’s alpha confirmed the reliability (α = 0.83) and strong internal consistency of PHPQ-18 scale. Conclusion These findings underscore the need for targeted interventions in university settings to address mental health and hygiene education. Further research should explore socio-economic and cultural factors influencing these relationships.